Alfred Hitchcock and the Three Investigators in The Mystery of the Silver Spider - Arthur, Robert (London Armada, 1972)
Three young detectives travel abroad to solve a mystery involving a silver spider and a political plot that endangers the life of a young prince.
Including illustration
Keywords: Detective and mystery stories -- Children's stories